Efficacy of scheduled intravenous acetaminophen administration for catheter-related bladder discomfort in patients after transurethral resection of bladder tumors: A prospective randomized pilot study - Tomoya Hatayama; Koji Mita; Yuki Kohada; Kenta Fujiyama; Ryo Tasaka; Akihiro Goriki; Hideki Mochizuki; Nobuyuki Hinata (Investigative and Clinical Urology)
Purpose: Scheduled administration of intravenous acetaminophen improves catheter-related bladder discomfort (CRBD) after urological surgery. However its efficacy for patients undergoing transurethral resection of bladder tumors (TURBT) remains unclear. This study aimed to investigate the efficacy of scheduled administration of intravenous acetaminophen after TURBT. Materials and Methods: At the end of surgery, patients in both the control (n=39) and the scheduled administration (n=45) groups received analgesics at the discretion of the anesthesiologists. In the scheduled administration group, intravenous acetaminophen was administered every 4 hours for 12 hours after the surgery. Both groups were administered on-demand analgesics as needed. The primary outcome was CRBD scores, and the secondary outcomes were the face rating scale for lower abdominal pain, administration rates of additional analgesics, durations of bladder catheterization, lengths of postoperative hospital stay, and postoperative complication rate. Results: The scheduled administration group had significantly lower CRBD scores than those of the control group at 8 hours postoperatively (p=0.014), and lower administration rates of additional analgesics 4–8 hours (p=0.029) and 8–12 hours (p=0.027) postoperatively compared to those of the control group. Other secondary outcomes were not significantly different between the groups (all p>0.05). The scheduled administration group did not have postoperative complications related to the scheduled administration of intravenous acetaminophen. Conclusions: Scheduled intravenous acetaminophen administration alleviated postoperative CRBD and reduced the need for additional analgesics in patients who underwent TURBT. These findings can be utilized to improve the quality of postoperative care.